Comparison of the analgesic efficacy of the ultrasound-guided transversalis fascia plane block and erector spinae plane block in patients undergoing open inguinal hernia repair under spinal anesthesia - Hale Kefeli Çelik; Serkan Tulgar; Ömer Faruk Bük; Kadem Koç; Murat Ünal; Caner Genç; Mustafa Süren (Korean Journal of Anesthesiology, 2024)
Background Open inguinal hernia repair (OIHR) surgery is a common surgical procedure, and ultrasound guided interfascial plane blocks can also be included in current approaches to postoperative multimodal analgesia regimens. This study aimed to compare the postoperative analgesic efficacy of the erector spinae plane block (ESPB) and transversalis fascia plane block (TFPB) in patients undergoing OIHR. Methods This prospective, randomized, assessor-blinded comparative study was conducted in the postoperative recovery room and ward of a tertiary hospital. A total of 80 patients with American Society of Anesthesiologists physical status I–III were enrolled and allocated equally to either the ESPB or TFPB group. The patients received standard multimodal analgesia in addition to an ultrasound-guided ESPB or TFPB. During the first 24 h postoperatively, tramadol consumption was assessed and pain levels at rest and during movement were compared using numeric rating scale (NRS) scores at 1, 3, 6, 9, 12, 18, and 24 h postoperatively. Results The results showed no difference in NRS scores at any time point between the groups, except for NRS at rest in the third hour. However, tramadol consumption was lower in the TFPB group than in the ESPB group overall (88 ± 75.2 vs. 131 ± 93.7 mg, respectively; P = 0.027, mean difference: −43, 95% CI [−80.82, −5.18]). Conclusions The TFPB leads to lower tramadol requirements in the first 24 h postoperatively than the ESPB in patients undergoing OIHR.